Dental caries and academic performance in schoolchildren from a Peruvian public educational institution - Sanchez Sandoval, Gabriela Aracely (2021)
Objective: To compare the prevalence of dental caries through the DMFT /dmft index with the low academic performance in schoolchildren  at a public school in Lima. Methods: Observational, analytical, cross-sectional, prospective design. The sample was made up of schoolchildren aged 10 to 12 from the Fortaleza de Vitarte Educational Institution No. 1239, from the period 2019. The sample size was made up of 136 schoolchildren who met the inclusion criteria. Dental evaluations were performed after dental hygiene and a record of the odontogram was taken using the DMFT / dmft index, to determine the presence of dental caries. Likewise, the record of grades was collected to obtain academic performance. Results: A high prevalence of dental caries was found in schoolchildren (94.9%), with moderate lesions prevailing (36.8%) compared to healthy teeth (5.1%). Likewise, the prevalence of carious lesions in children aged 11 years (50.7%), followed by 12 years (26.5%) and 10 years (22.8%), an increase is observed between the ages of 10 years and 11 years. In addition, a low academic performance of (10.3%) was presented, being the distribution in males (6%) and in females (3.7%). It was found that the DMFT +dmft are homogeneous in approved children and children with low performance both in age and sex, meaning that there is no statistically significant difference between both variables (p> 0.05). Conclusion: Despite the high prevalence of dental caries, it does not show a correlation with low academic performance in schoolchildren aged 10 to 12 according to the DMFT / dmft index.